2009
DOI: 10.1016/j.jjcc.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction, increased carotid artery intima-media thickness and pulse wave velocity, and increased level of inflammatory markers are associated with variant angina

Abstract: VA is associated with endothelial dysfunction and increased carotid IMT, baPWV, and inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…These patients had higher hs-CRP serum levels, increased mean common CIMT, and increased arterial stiffness [34]. In another study, endothelial dysfunction was associated with increased CIMT and PWV [35].…”
Section: Discussionmentioning
confidence: 90%
“…These patients had higher hs-CRP serum levels, increased mean common CIMT, and increased arterial stiffness [34]. In another study, endothelial dysfunction was associated with increased CIMT and PWV [35].…”
Section: Discussionmentioning
confidence: 90%
“…Loss of adequate endothelial cell function is most widely quantified by assessing FMD and NMD. Previously, we reported that decreased FMD and increased carotid IMT and PWV were associated with CAD 18. In particular, the dilatory response to NTG is used as a measure of endothelium-independent vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was unable to explore this association. Previously, several clinical and hemodynamic studies using nitrate were published in Korea 18,26-29. However, the clinical impact and mechanisms are not exactly known.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the study, FMD was measured by the same skilled examiner, who used the same ultrasound apparatus and probe set. We have previously reported inter-study coefficient of variation (CV) of 9% for FMD measurements (Cho et al, 2009). …”
Section: Brachial Flow-mediated Artery Vasodilatationmentioning
confidence: 99%
“…These benefits attribute to its pleiotropy, including modulation of endothelial function, alleviation of arterial stiffness, and stabilization of plaque (Cho et al, 2009). Pitavastatin calcium has been described as a "super statin" with stronger low-density lipoprotein cholesterol (LDL-C)/ triglyceride (TG)-lowering and high-density lipoprotein (HDL)-elevating effects compared with other statins at the initial dose.…”
Section: Introductionmentioning
confidence: 99%